The Role of Transient Receptor Potential Vanilloid 1 in Common Diseases of the Digestive Tract and the Cardiovascular and Respiratory System - Du, Qian; Liao, Qiushi; Chen, Changmei; Yang, Xiaoxu; Xie, Rui; Xu, Jingyu (Frontiers in Physiology, 2019)
Transient receptor potential vanilloid subtype 1 (TRPV1), a member of the transient receptor potential vanilloid (TRPV) channel family, is a non-selective cation channel and that is widely expressed in sensory nerve fibers and nonneuronal cells, including certain vascular endothelial cells and smooth muscle cells. The activation of TRPV1 may be involved in the regulation of various physiological functions, such as the release of inflammatory mediators in the body, gastrointestinal motility function, and temperature regulation. In recent years, a large number of studies have revealed that TRPV1 plays an important role in the physiological and pathological conditions of the digestive system, cardiovascular system, and respiratory system, but there is no systematic report of TRPV1.The objective of this review is to explain the function and affection of TRPV1 in specific diseases, such as irritable bowel syndrome, hypertension, and asthma, and further investigates the intrinsic relationship between the expression and function of TRPV1 in those diseases, in order to find new therapeutic targets for the cure of related diseases.